Peripubertal exposure to male chemosignals accelerates vaginal opening and induces male-directed odor preference in female mice - Jouhanneau, Mélanie; Goudet, Camille; Moussu, Chantal; Tashiro, Takuya; Buatois, Bruno; Mori, Kenji; Ganem, Guila; Keller, Matthieu (Frontiers in Ecology and Evolution, 2015)
Reproductive physiology in female mouse is profoundly affected by male odor. A well-known effect of male odor is the acceleration of puberty onset in prepubertal female mice exposed to male urine. Whether peripubertal exposure to male odor also influences female sexual behavior in adulthood is poorly known. Recently, we reported that female mice exposed to male-soiled bedding showed advanced vaginal opening associated with early expression of male-directed odor preference in adulthood. The aim of the present study is to determine whether peripubertal exposure to male urinary chemosignals affects both occurrence of vaginal opening and attraction to male odor at older age in female mice. Therefore, we exposed female mice to (1R, 5S, 7R)-3,4-dehydro-exo-brevicomin (DHB), 6-hydroxy-6-methyl-3-heptanone (HMH) and (S)-2-sec-butyl-4,5-dihydrothiazole (SBT), individually or in mixture, from postnatal day (PD) 21 to PD38 and monitored the occurrence of vaginal opening. We measured then the time that the female mice spent sniffing male and female mouse urinary volatiles at PD45. As expected, peripubertal exposure to DHB, HMH or SBT accelerated vaginal opening in female mice. In addition, we showed that exposure to a mixture of these three compounds induced expression of male-directed odor preference at PD45, contrary to the single exposure to each of these molecules. In conclusion, the volatile compounds DHB, HMH and SBT in urine of male mice influence both occurrence of vaginal opening and adult expression of male-directed odor preference in female mice.